Utilization of Conceptual and Theoretical Framework in Research by Nurse Educators in Akwa Ibom and Cross River States, Nigeria (Global Journal of Medical Research, 2015)
Abstract not found
Keywords: conceptual-framework; education; knowledge; nurse-educators; nursing; professionalism; research; training; theoretical-framework; utilization